B cell contribution of the CD4+ T cell inflammatory phenotypes in systemic lupus erythematosus. (2nd January 2017) - Choi, Seung-Chul; Morel, Laurence
Abstract: Systemic lupus erythematosus is an autoimmune disease in which the effector molecules responsible for tissue damage are antibodies directed against a large number of self-antigens, among which nucleic acids complexed with proteins play a prominent role. These pathogenic autoantibodies are produced by plasma cells differentiated from activated autoreactive B cells, a process that requires complex interactions between multiple components of the immune systems. A key step in the activation of autoreactive B cells is provided by CD4 +  T cells through cytokines and cell-to-cell contact. Lupus CD4 +  T cells are autoreactive and they present an activated inflammatory phenotype that has been shown to contribute to disease. In addition to their role in antibody production, B cells have other effector functions, the most important ones being antigen presentation to and co-stimulation of CD4 +  T cells, as well as the secretion of cytokines. Here, we review what is known, largely based on mouse models, how these B cell effector functions contribute to the CD4 +  T cell inflammatory phenotypes in lupus. When possible, we compare CD4 +  T cell activation by B cells and by dendritic cells, and speculate how these interactions may contribute to the disease process.